A invenção do aluno: a implantação do Primeiro Gymnasio da Capital, em São Paulo (1894-1917) - Cabral, Maria Aparecida da Silva (2002)
This reseach dates from the period known as the First Republic, When happened, an expressive Ipreading of theaching in São Paulo. This was also the stage which transformed the school in a powerful tool of acting fram the goverments of São Paulo, in order to aceomplish and make real a proposal of modernization. This way, as the school was the privileged stage of the republicans, its subjects were also cause of intervention. So, one intends to search, at the first gymnasium of the Capital, the origin of a new personage: the pupil; as well as to verify, Starting from the construction of disciplinary norms, as well as different strategies. control, adopted by this institution in the process of its legitimacy. In the prospect of constructing a look that moves itself, from the educational reforms to the questioning in view of the internal feature of the scholar institution. This inquiry trys to contribute to unveil a dimension not much exploited in the studies, in the arece of the Education History - the scholar practices. We have as dim to reved that the scholar space is constituted by resistances, adjustments, infringements by its subjects. By this way, we utilized a documentation that made possible the rebuilding of the trajectory of these scholars: official letters sent to the parents reports about the disciplinary behave marks bulletins, registration books frequency book, the first gymnasium of the Capital Congregations Ata, and to go inside the thoughts and pedagogical practices, which circulated and guided the Scholar practices me analized the Public teaching Rule (1982), and the Gymnasium' s Rule of the State of São Paulo (1985)